THE LIFE AND THE SCIENTIFIC ACTIVITY OF NURIDDIN AL-SABUNI AXMEDOV ANVAR (World Conference on Social Sciences, Law and Public Policy, 2026)
The purpose of the study will be the scientific activity of Nuriddin Al-Sabuni, his lifestyle, researches and the role they play in framing the teaching of Maturidiyya. This article also considers to familiarize the reader with the context of some of the research works carriesin that time. It is important to point out that most of manuscripts of his books saved in Turkey exist within the libraries that are specifically oriented in kalam studies, but tend to give a general religious higher education, especially, aqeedah teachings.
Keywords: Nuriddin Al- Sabuni, the teaching of Maturidiyya, kalam school, Fakhriddin Razi, Süleymaniye Library, Kardari, Al-Kifaya filkhidaya, prophets